A "MÍSTICA DO PIONEIRISMO", ANTÍDOTO CONTRA O SOCIALISMO: BENTO MUNHOZ DA ROCHA NETO, A REFORMA AGRÁRIA E O NORTE DO PARANÁ DOS ANOS 50 E 60 (Revista de História Regional, 2007)
During the fifties and sixties, the North of Parana was transformed by political and national sectors into models of agrarian reform adapted to assumed interests and tendencies of the Brazilian people. These formulations, which are sometimes against to those considered in the rural (and urban) working-class movements, involve the construction of social categorisations related to the pioneers from the regional settlement. The ex-governor of Parana, Bento Munhoz da Rocha Neto, was one of the great producers and divulgers of the vision of the region and its inhabitants. In this article we study some of the is positions and their cognitive effects on the so called public opinion.